Particulate and non-particle adjuvants in Leishmaniasis vaccine designs: A review - Kelleci, Kubra; Allahverdiyev, Adil; Bagirova, Melahat; Ihlamur, Murat; Abamor, Emrah S. (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2023)
Leishmaniasis is a parasitic disease with different clinical forms caused by protozoan parasites of the genus Leishmania and transmitted by the bite of an infected female sandfly. According to the World Health Organization (WHO), it is the second most common parasitic disease after malaria and it is known that approximately 350 million people are at risk. The disease manifests itself in different clinical forms. In addition to asymptomatic cases, cutaneous leishmaniasis (CL), which creates large lesions on the skin, and visceral leishmaniasis (VL), which causes death if not treated, especially affecting the abdominal organs, are two important clinical forms. When the studies were examined, it was seen that a clinically used vaccine against any form of human leishmaniasis has not been developed yet. In some studies, it was stated that the lack of appropriate adjuvant was responsible for the failure to develop an effective Leishmania vaccine. We can say that strong adjuvants are needed to achieve successful vaccines. In this article, adjuvants and adjuvant candidates used in vaccine studies against leishmaniasis are discussed
Keywords: leishmaniasis; adjuvant; vaccination; delivery system; nanoparticles; SOLID-LIPID NANOPARTICLES; CPG ODNS INDUCE; IMMUNE-RESPONSE; CUTANEOUS LEISHMANIASIS; VISCERAL LEISHMANIASIS; PROTECTIVE IMMUNITY; MURINE MODEL; BALB/C MICE; ANTILEISHMANIAL ACTIVITIES; RECOMBINANT PROTEIN; Infectious Diseases; Parasitology; Tropical Medicine